2019
DOI: 10.1080/02615479.2019.1584176
|View full text |Cite
|
Sign up to set email alerts
|

How is ‘racism’ understood in literature about black and minority ethnic social work students in Britain? A conceptual review

Abstract: H o w is ' r a ci s m ' u n d e r s t o o d in lit e r a t u r e a b o u t t h e e x p e ri e n c e s of bl a c k a n d m i n o ri ty e t h ni c s o ci al w o r k s t u d e n t s in B rit ai n ? A c o n c e p t u al r e vi e w Jey a si n g h a m , DJ a n d M o r t o n, JW h t t p:// dx. d oi.o r g/ 1 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…There have been a number of problems identified in relation to institutionalised racism. Some have noted criticism that its emphasis on covert racism could deflect attention from more overt forms (Phillips, 2011) and that it has been collapsed with “subtle” forms of racism that, while covert, micro-aggressive instances, are not necessarily part of the warp-and-weft of an institution (Jeyasingham and Morton, 2019). Other critics, academic and professional, have focused on conceptual ambiguity (Souhami, 2014): more specifically, a clear lack of consensus about its meaning, which enabled the Police Commissioner at the time of the Macpherson inquiry, Paul Condon, some traction in arguing against its efficacy as a means of understanding police service policy and practice (Rowe, 2012).…”
Section: Macpherson and Institutionalised Racism: Where Are We Now?mentioning
confidence: 99%
“…There have been a number of problems identified in relation to institutionalised racism. Some have noted criticism that its emphasis on covert racism could deflect attention from more overt forms (Phillips, 2011) and that it has been collapsed with “subtle” forms of racism that, while covert, micro-aggressive instances, are not necessarily part of the warp-and-weft of an institution (Jeyasingham and Morton, 2019). Other critics, academic and professional, have focused on conceptual ambiguity (Souhami, 2014): more specifically, a clear lack of consensus about its meaning, which enabled the Police Commissioner at the time of the Macpherson inquiry, Paul Condon, some traction in arguing against its efficacy as a means of understanding police service policy and practice (Rowe, 2012).…”
Section: Macpherson and Institutionalised Racism: Where Are We Now?mentioning
confidence: 99%
“…Singh's (2019) study exploring the outcomes of anti-racist social work education concluded that when the right teaching approaches are employed that include intercultural dialogue and unravelling unconscious bias, this enables deeper racial consciousness and self-examination, alteration in attitudes, insights, and gaining the right knowledge and skills for practice. However, Jeyasingham and Morton's (2019) literature review identified the scarcity of social work literature exploring teaching practices that reflect on racial history, discourse and narratives. Their work is supported by Arday et al (2020), who conducted a study with Russell University student participants and concluded that classroom discourse and conversations on race are a helpful step to understand the realities of colonial struggle, and to think creatively and collectively about decolonisation as well as to support minority ethnic students with their day-to-day struggles with institutional racism.…”
Section: Racial Consciousness and Teaching Practicesmentioning
confidence: 99%
“…Their work is supported by Arday et al (2020), who conducted a study with Russell University student participants and concluded that classroom discourse and conversations on race are a helpful step to understand the realities of colonial struggle, and to think creatively and collectively about decolonisation as well as to support minority ethnic students with their day-to-day struggles with institutional racism. They assert that both students and social workers need to be more conscious and reflective about their own positionality and look deeper into racial constructs and how these manifest into oppression (Jeyasingham and Morton, 2019). The pedagogies employed in this project encouraged participants to actively reflect upon the challenges of racialised experiences and differences in identities.…”
Section: Racial Consciousness and Teaching Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…By the beginning of the 21 st century, the anti-racism movement within social work in Britain was replaced by an emphasis on diversity, equality and cultural competence -a move that Jeyasingham and Morton (2019) argues was utilized to provide superficial evidence of social equality. One of the unfinished tasks of the anti-racist social work movement in Britain was changing the culture and structure of organizations (Singh, 2011).…”
Section: Removing the Knees From Their Necks: Adopting Anti-racist Somentioning
confidence: 99%